Soil compaction with wheels of manure spreader aggregates - Marczuk, Aneta; Kamiński, Jan Radek; Viselga, Gintas; Turla, Vytautas; Jasinskas, Algirdas; Ugnenko, Evgenija (Transport, 2021)
The study focused on the definition of the impact of the parameters of the applied manure spreaders (loading capacity, size of tyres, the number of driving wheels) on the numerical values of the basic exploitation indices and on soil compaction as well. Research tests were carried out on farms of different arable land areas. The scope of the study included questionnaire surveys, laboratory and exploitation tests, comparison evaluation of fertilization units, verification of the acquired results, as well as recommendation for practical use. A significant growth in productivity (from 0.38 to 1.15 ha/h) was observed together with an increase in the loading capacity of the spreaders, but the following indicators were found to have decreased: surface of soil compaction (from 44 to 15%), field loading (from 412 to 165 kN∙km) and grooves volume (from 165 to 67 m3). Four-wheel spreader of 20 t loading capacity has been characterized by two times higher values of field loading indices (357 kN∙km), groove loading (204 kN/m) and groove volume (110 m3) in comparison with a two-heel spreader with a loading capacity of 10 t.First published online 19 January 2022